The Roles of Parents Teachers Association in School-Age Children’s Psychosocial Development According to Erik Erikson - Sendi Wijaya (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
People these days tend to avoid their attention from child’s psychosocial development while it holds serious role for the psyhcological and social development of children to find their true identity in the future. According to Erik Erikson, there are 8 stages of phsychosocial development of human starts when a human being is born to the final stage which is at 65 years old above. In this theory, Erikson emphasizes that every stage holds its importance and that they relate each other. Which means the first stage affects the next stage and so forth. This research is aimed to analyze Erikson’s 8 stages development of psychosocial on school-age children and how parents and teachers should respond and provide suitable treatment for these children.The methodology in this research is literature research where author collects the information about 8 stages psychosocial development from journal, books, reviews, or previous research. From this research, author finds that parents must give proper and suitable parenting style for their child especially during their school periods where child needs support, motivation and stimulus either from parents or teachers or their surroundings through intensive communication. For addition, through this research too, author finds that the ability for teachers to understand these 8 stages will give them the sight to provide more chances for the children to grow well and find their true identity. From this research, we can conclude that either teachers and parents need to cooperatively work together to provides proper and suitable treatment for children’s psychosocial development according to Erikson’s 8 stages development.